Strategic sourcing in the public sector - Grilli, Barbara A.; Webb, Theresa G. (New York Routledge, 2023)
Effective sourcing in the public sector is a collaborative and strategic process that does not end when the contract or purchase order is executed. As an ongoing process of improvement, strategic sourcing requires regular appraisals of procurement activities to ensure they continue to support the goals of the entity. Strategic Sourcing in the Public Sector explains the theory behind sourcing. Why does sourcing need to be strategic, and what are the stakeholders' roles in the process? Written to complement the Institute of Public Procurement's (NIGP) Sourcing and Solicitation curriculum, this book explores the impetus or the 'why' behind the sourcing process as well as the 'how.'

The book walks the reader through all of the important considerations for any sourcing process, including requirements analysis, stakeholder involvement, scope of work, sourcing documents and approvals, and supplier relationship management to name a few. Throughout the book, students and practicing professionals are encouraged apply principles of procurement to diverse situations. Because of its user-friendly language and approach, Strategic Sourcing the Public Sector is accessible to those new to the procurement profession, individuals seeking certification, and undergraduate and graduate students enrolled in public administration programs. At the same time, the rich content based on NIGP's public procurement competency framework provides value for seasoned professionals with substantial experience and specialized knowledge.
Overview -- Strategic Sourcing -- Guidelines for Strategic Sourcing -- Requirements Analysis -- Sourcing for Stakeholders -- Scope of Work -- Sourcing Methods, Business Approaches, and Processes -- Sourcing Documents and Approvals -- Authorizations, Approvals, and Award -- Supplier Relationship Management -- Conclusion -- Index.
Includes bibliographical references and index.
Keywords: Contracting out; Government purchasing; Public contracts; Strategic planning